Assessing the Institutional Capacity of the Indonesian State: Taxation Reform since 2002 - Rismawanti, Inge Diana (Curtin University, 2019)
Much of the literature has perceived the Indonesian government as a patrimonial state. This thesis examined the effectiveness of taxation reform to find out how reform has improved the state capacity in a way that supported main government revenues and that increasing government expenditure in providing public goods and services could be safeguarded. The process of tax reform has indeed influenced reform in other areas of government towards a rational legal administration system of bureaucracy.